Analisis Perubahan Ruang Terbuka Hijau dan Faktor-Faktor yang Memengaruhinya di Kota Surakarta - Septita Dwi Listanti; Rachmad Hermawan; Yudi Setiawan (Jurnal Penelitian Pendidikan IPA, 2025)
Green Open Space (GOS) is a critical urban element, but the legally mandated minimum 30% area is often unmet. This study aims to analyze the changes in the GOS area from 2002, 2013, and 2024 and the factors influencing it. GOS area change was analyzed using the delineation method on high-resolution satellite imagery from Google Earth Pro, and the results showed that the area of GOS in Surakarta City in 2002 was 360.95 ha, in 2013 was 341.18 ha, and in 2024 was 328.76 ha. Logistic regression analysis was applied to model the influence of explanatory variables, resulting in findings that distance to the road, distance to settlements, distance to transportation facilities, and population density are significant variables influencing GOS decline. Although these variables only explained 9.1% of the change, this suggests that there could be other external factors affecting GOS that have not been analyzed in this study. The local government needs to strengthen policies, tighten building permit supervision, and ensure consistency with Regional Spatial Planning to optimize existing GOS and develop new GOS in potential locations to address the deficit of approximately 1,072.84 ha.